1998
DOI: 10.1093/jjco/28.3.196
|View full text |Cite
|
Sign up to set email alerts
|

Growth Patterns and Genetic Changes of Colorectal Carcinoma

Abstract: Background: Recent Japanese studies have shown that histogenesis of small colorectal carcinomas can be divided into two groups: polypoid growth arising from polypoid neoplasia, and non polypoid growth arising from flat or depressed neoplasia. This classification should be verified with genetic as well as morphologic characteristics. Subjects and Methods: In order to classify our subject into polypoid growth and non polypoid growth types both histologically and endoscopically, we selected 42 colorectal carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…In the present study, we investigated the clinicopathological characteristics of small advanced carcinomas ≤ 2 cm in diameter ; in our previous study we focused on the progression of at and depressed lesions. We previously suggested that the progression of NPG carcinomas occurs via a different pathogenetic pathway from that of PG carcinomas 7,8,22,23 . Apart from differences in macroscopic ndings, we also demonstrated that genetic alterations of NPG carcinomas were different from those of PG carcinomas, even at an advanced stage 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we investigated the clinicopathological characteristics of small advanced carcinomas ≤ 2 cm in diameter ; in our previous study we focused on the progression of at and depressed lesions. We previously suggested that the progression of NPG carcinomas occurs via a different pathogenetic pathway from that of PG carcinomas 7,8,22,23 . Apart from differences in macroscopic ndings, we also demonstrated that genetic alterations of NPG carcinomas were different from those of PG carcinomas, even at an advanced stage 7 .…”
Section: Discussionmentioning
confidence: 99%
“…1, 2 . Details of the assessment procedure have been described previously 8 . Brie y, formalin-xed surgical specimens were cut into blocks 5 mm in thickness and embedded in paraf n for sectioning.…”
Section: Classi Cation Of Tumors As Pg or Npg Carcinomasmentioning
confidence: 99%
“…Classification criteria for PG and NPG Some minute nonpolypoid intramucosal neoplasias have been reported to transform to nonpolypoid invasive cancers (Minamoto et al, 1994;Matsumoto et al, 1995;Fujiya and Maruyama, 1997). In our previous study, almost all of NPG carcinomas infiltrating the submucosa were macroscopically flat and depressed carcinomas (Kaneko et al, 1998). We thought that PG and NPG carcinomas infiltrating the submucosa would progress PG and NPG carcinomas infiltrating beyond the submucosa.…”
Section: Patient Selection and Data Collectionmentioning
confidence: 93%
“…Histologically, the resected tumour was a moderately differentiated adenocarcinoma infiltrating through the muscularis propria ( Figure 1C) with metastases to regional lymph nodes (stage III, T3N1M0). This carcinoma was classified as having a nonpolypoid growth (NPG) pattern according to our previously published criteria (Kaneko et al, 1998). While no frameshift mutation of the APC gene and no Ki-ras mutation were present, a p53 mutation was found in exon 7 (codon 244; base change, GGC to GAC; amino-acid change, Gly to Tyr).…”
Section: Initial Casementioning
confidence: 99%
See 1 more Smart Citation